A tradição Intelectual do Romance Vida e Morte de M. J. Gonzaga de Sá, de Lima Barreto - Pontes, Deysiane Farias (2009)
This research aims to study the intellectual tradition in the novel Vida e Morte de M. J. Gonzaga de Sá, Lima Barreto, published in 1919. This narrative is presented as Gonzaga de Sá’s biography, from a traditional family, clerk, dedicated to the study of different forms of knowledge. The biographer and narrator-character, Augusto Machado, is a young mulatto, Gonzaga’s friend. However, the biography is not structured like the others: what most matters is not the personal life facts, but the protagonist’s intellectual life and conflicts. The intellectual tradition functions as the legacy left by Gonzaga de Sá to Augusto Machado. The narrator writes the biography as one who organizes an intellectual inventory. As the study method, we divided the intellectual tradition in this work into: philosophical, historical and literary. In the first chapter, we analyze the philosophical tradition, represented by Francis Bacon ,Arthur Schopenhauer, Jean-Jacques Rousseau and Friedrich Nietzsche. It is reflected, among other things, about the possibility of action in the world, a recurring theme in Lima Barreto’s work. In the second chapter, we studied the reflections on the history and the memory of the city, the political situation of the First Brazilian Republic and the theories about the workers. In the last chapter, we discuss the literary tradition in Vida e Morte… composed by the writers in the Western canon. Thus, it is noticed that the intellectual tradition in Vida e Morte... represents the formation of the Brazilian intellectual, the main questions from the early twentieth century and the characters’ nonconformity when demonstrating critical ability on the reflections that combine facts from Brazilian reality and the Western intellectual thought.